A review study of substance abuse status in high school students, Isfahan, Iran - Mah Monir Nahvizadeh; Shohreh Akhavan; Sara Arti; Leila Qaraat; Nahid Geramian; Ziba Farajzadegan; Kamal Heidari (International Journal of Preventive Medicine, 2014)
Background: As the first experience of substance abuse often starts in adolescence, and studies have shown that drug use is mainly related to cigarette and alcohol consumption, an initial exploration of substance abuse prevalence, including cigarette and alcohol, seems to be the first step in preventing and controlling drug consumption. This study aimed to explore studies on drug use among high school students by investigating articles published in the past decade in Iran. Methods: In this study, the databases inside the country were used to access articles related to substance abuse by students during 2001-2011, among which 7 articles on 14-19 years old high school students were studied. Results: The seven studied articles showed that the highest drug use prevalence pertained to cigarette and hookah, followed by alcohol, opium, ecstasy, hashish and heroin. Opium and heroin use in Kerman city were, respectively, about 4 and 5 times of their use in other studied cities. Conclusions: Drug use is relatively high in the adolescent and effective group of the society, which requires particular attention and prompt and immediate intervention.